2022
DOI: 10.3390/molecules27010261
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Magnetic Nanoparticles Functionalized with Anti-Folate Receptor Antibody and Methotrexate for Antibody Mediated Targeted Drug Delivery

Abstract: Therapeutic effects of anticancer medicines can be improved by targeting the specific receptors on cancer cells. Folate receptor (FR) targeting with antibody (Ab) is an effective tool to deliver anticancer drugs to the cancer cell. In this research project, a novel formulation of targeting drug delivery was designed, and its anticancer effects were analyzed. Folic acid-conjugated magnetic nanoparticles (MNPs) were used for the purification of folate receptors through a novel magnetic affinity purification meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…High doses of MTX have been reported to generate a state of oxidative stress capable of damaging biomolecules, inducing cancer cells death 38 ; this mechanism is independent on folic acid conversion to tetrahydrofolate by inhibiting the dehydrofolate reductase (DHFR) activity, an essential enzyme in DNA synthesis mechanisms. 38 , 39 On the other hand, treatment with low concentrations of MTX is known to reduce inflammation, decrease apoptosis, and induce proliferation by inhibiting NF-κB and PI3K/Akt. 40 Studies using HUVEC cells treated with TNF-α have shown that low concentrations of MTX induce the expression of survival genes such as SOD-Mn, OH-1, UCP-2, which are regulated by AMPK-CREB.…”
Section: Discussionmentioning
confidence: 99%
“…High doses of MTX have been reported to generate a state of oxidative stress capable of damaging biomolecules, inducing cancer cells death 38 ; this mechanism is independent on folic acid conversion to tetrahydrofolate by inhibiting the dehydrofolate reductase (DHFR) activity, an essential enzyme in DNA synthesis mechanisms. 38 , 39 On the other hand, treatment with low concentrations of MTX is known to reduce inflammation, decrease apoptosis, and induce proliferation by inhibiting NF-κB and PI3K/Akt. 40 Studies using HUVEC cells treated with TNF-α have shown that low concentrations of MTX induce the expression of survival genes such as SOD-Mn, OH-1, UCP-2, which are regulated by AMPK-CREB.…”
Section: Discussionmentioning
confidence: 99%
“…FR-based delivery vehicles are internalized by target cells through receptor-mediated endocytosis. As a result, drug-loaded nanocarriers may be tailored to target particular cancer cell receptors, employing targeting ligands such as folic acid (FA) [ 41 , 42 , 43 ]. FA is a well-known vitamin for cell proliferation and biomarker targeting.…”
Section: General Overview Of Breast Cancermentioning
confidence: 99%
“…The utilization of antibody-bound MIONPs hinted at the potential to create a targeted thermal treatment for metastatic cancer by means of induction heating with an external alternating magnetic field. Tests were conducted employing (111) In-ChL6 bio-probes (a chimeric L6) in an artificial xenograft model for human breast cancer [82]. Another [83] examination administered Herceptin (trastuzumab) to transport ferric oxide-enriched NPs to Human Epidermal Growth Factor Receptor 2 (HER-2+) cancer cells.…”
Section: Targeting Cancer Cells With Mnps For Mhtmentioning
confidence: 99%